2005
DOI: 10.1007/s11010-005-4508-8
|View full text |Cite
|
Sign up to set email alerts
|

5?-reductase in human embryonic kidney cell line HEK293: Evidence for type II enzyme expression and activity

Abstract: Human 5alpha-reductase catalyses the last step in androgen biosynthesis, namely the reduction of testosterone (T) to the more potent androgen dihydrotestosterone (DHT). The enzyme is therefore considered to be an important drug target for androgen related diseases such as benign prostatic hyperplasia and prostate cancer. The present study displays evidence that the human embryonic kidney cell line HEK293 which is frequently used in recombinant target protein expression contains an endogenous 5alpha-reductase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Some authors have reported that human SRD5A1 is associated with nuclear fractions upon expression in insect Sf9 cells [28] , [29] but later papers [30] have instead reported retrieval of enzyme activity from the microsomal fraction. Expression of SRD5A2 and SRD5A1 in HEK293 and in LNGK-9 PCa cells yielded activity in the nuclear and microsomal fractions [31] , [32] . Upon heterologous expression and purification in yeast, SRD5A1 appears to be associated to nuclei, whereas SRD5A2 is in the microsomal fraction [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported that human SRD5A1 is associated with nuclear fractions upon expression in insect Sf9 cells [28] , [29] but later papers [30] have instead reported retrieval of enzyme activity from the microsomal fraction. Expression of SRD5A2 and SRD5A1 in HEK293 and in LNGK-9 PCa cells yielded activity in the nuclear and microsomal fractions [31] , [32] . Upon heterologous expression and purification in yeast, SRD5A1 appears to be associated to nuclei, whereas SRD5A2 is in the microsomal fraction [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Although classed as non-steroidogenic, previous studies have shown the endogenous expression of some enzymes in the HEK293 cell line. While not observed in the present study, one such enzyme includes SRD5A which catalyses the reduction of the C4/C5 double bond [ 17 , 51 , 52 ]. However, conversion of 11OH5αdione by 11βHSD2 in the present study yielded both 11K5αdione and 11KDHT, suggesting the expression of endogenous 17βHSD isozyme/s, which was also reported in a previous study by our group [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory activity of Leuzea root extract and 20-hydroxyecdysone towards 5α-reductase, type II was determined using HEK-II cell homogenates and substrate 1β[ 3 H]-androstenedione (505 nM) as well as the well known 5α-reductase inhibitor finasteride as positive control (IC 50 = 25 nM) as previously described [18], [19].…”
Section: α α-Reductase Inhibitory Activitymentioning
confidence: 99%